Implementasi Algoritme SPECK pada Wireless Sensor Network menggunakan Media Pengiriman Data nRF24L01 - Retno Nizma'urrahmi; Ari Kusyanti; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Wireless Sensor Network (WSN) is a network formed by several sensor nodes and wirelessly connected to each other with the limitations of each node. One of the limitations of the resources contained in the WSN node is the communication media. This causes WSN to require a data communication method with low resource usage. The nRF24L01 module is designed of being implemented in a wireless network that has low resources, so that it can be applied to a WSN network. The nRF24L01 module will broadcast or broadcast at an address to transmit data. Then, to receive data, a listen process is carried out so that it can be received by devices that are at the same address as the sender. This causes a security hole when a device is intended to send data to the desired device only. For this reason it is necessary to have a mechanism that can ensure the security of ongoing data communications. The SPECK algorithm has been tested on both hardware and software by the National Security Agency (NSA). The SPECK algorithm has been optimized to run on the software. Users can implement SPECK Cipher by considering the application and hardware required without compromising performance. The purpose of the SPECK algorithm itself is to provide the flexibility and performance characteristics required by developers. The implementation of the SPECK algorithm on the system makes this system resistant to both passive and active attacks.